Optimization of Warehouse Operations for Upstream Service Companies in the Oil & Gas Industry: A Case Study of XYZ Company - Daud, Mohd Radzi Mohd; Zulfakar, Mohd Hafiz (Information Management and Business Review, 2024)
The oil and gas (O&G) sector drives various parts of Malaysia’s economy and accounts for 19% of government revenue in 2021. The volatility of oil prices and the COVID-19 pandemic problem in recent years has taught O&G enterprises, especially upstream players, to focus on business needs and employ cost optimization techniques to compete and survive uncertain circumstances. This study seeks to analyze and describe the warehouse operations setup of an onshore supply base service organization that manages and maintains offshore O&G facilities. This study examines space utilization variables from several supply chain perspectives, particularly operations performance. Semi-structured interviews, site observations, and documentation review are used to collect data for the single-case study. The study findings suggest the organization under study has a basic warehouse setup with lean operations staff to complete business functions. In general, the warehouse arrangement for the organization under investigation is comparable to a distribution center, where 70% of warehouse activities comprise, material receiving, handling, and distribution (loading) to several offshore locations. Findings also showed that two factors, namely: material handling flow and movement, and inventory movement affect warehouse space utilization. The volume of material handled by the warehouse based on business demand, as well as the seasonal trend from offshore activities contribute to the frequency of material loading and impact the material throughput and transit time, which were found to have an impact on space utilization too.